History of the Christian church ; v.4 - Sheldon, Henry C. (Peabody, MA Hendrickson, 1988)
Contents : v.4 : The modern church ; pt 2 : 18th century. Includes bibliographical references and indexes.
Reprinted from the original edition, published 1895, Thomas Y. Crowell and Co., New York.
Keywords: Church history -- 18th century